Impact of partial alteration of diesel fuel on the performance and regulated emission of a diesel engine - Mizanur Rahaman; Md Ikramul Hasan; M. Mofijur; M.G. Rasul; N.M.S. Hassan; Hwai Chyuan Ong (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2021)
Biodiesel has become one of the promising solutions for the future energy crisis. This study aims to assess the effect of alteration of fuel (replacing diesel with biodiesel) on the performance and regulated emission in a diesel engine. Biodiesel blends (WCB20) was prepared by mixing 20% of waste cooking oil biodiesel with 80% diesel fuel using a homogeneous mixture. The performance and regulated emission of WCB20 have been evaluated in a multi-cylinder diesel engine at various speeds with a full load condition and compared with diesel fuel. The results indicated that WCB20 offers 6.52% less brake power and 9.01% lower brake thermal efficiency whereas, 36.15% and 32.16% higher BSFC and BSEC in comparison to diesel fuel, respectively. However, regulated emission results showed that WCB20 significantly decrease carbon monoxide, particulate matter, and hydrocarbon by 38.93%, 15.46%, and 21.20% respectively but slightly increase the NOx emission (13.79%). Finally, it can be concluded that partial alteration of conventional diesel fuel using 20% waste cooking oil biodiesel can indicatively reduce the harmful emission.